Mites and merchants: the crisis of English wool and textile trade revisited, c. 1275–1330. (15th March 2020) - Slavin, Philip
Abstract: On the basis of 7, 871 manorial accounts from 601 sheep‐rearing demesnes and 187 tithe receipts from 15 parishes, this article addresses the origins, scale, and impact of the wool and textile production crisis in England, c . 1275–1350. The article argues that recurrent outbreaks of scab disease depressed sheep population and wool production levels until the early 1330s. The disease, coupled with warfare and taxation, also had a decisive role in depressing the volumes of wool exports. Despite this fact, wool merchants were still conducting business with major wool producers, who desperately needed access to the capital to replenish their flocks.